The Implementation of Vulva Hygiene Treatment in Postpartum Women to Prevention of Rupture Perineum Infection - Fitriani Sangkala; Andi Sriwardana (Newinera Publisher, 2020)
Perineal rupture or tear of the birth canal is usually experienced by postpartum mothers or mothers in labor. Either because of the episiotomy or naturally due to the pressure of the fetal head. Perineal rupture affects women’s physical. The impact of perineal rupture in women who are not properly treated is infection perineum. As the treatment efforts that can be done to prevent infection, namely by performing vulva hygiene care. The research explores quantitative evidence published in an electronic database, Google Scholar. Studies have shown that proper care of vulva hygiene can be 10 times greater in preventing infection in perineal rupture. The results showed that vulva hygiene treatment was able to prevent infection in perineal rupture.